Extended Model on Structural Stability and Robustness to Bounded Rationality - Yi Liao; Lujiang Miao; Lei Wang; Fei Xu; Chi Zhang (Complexity)
In this article, we focus on an extended model M¯ of bounded rationality. Based on a rationality function with lower semicontinuity, we analyze the relationship between structural stability and robustness of Ω¯. To further demonstrate the applicability of our theory, we introduce a model Ω¯0 containing an abstract rationality function and generalize abstract fuzzy economies. We demonstrate the structural stability of the extended model Ω¯0 at ξ¯,ɛ. That is to say, Ω¯0 is robust to the ξ¯,ɛ-equilibria.